Validation of an External Support for Coronary Artery Saphenous Vein Grafts without Fibrin Sealant - Suwalski, Grzegorz; Emery, Robert W. (The Thoracic and Cardiovascular Surgeon, 2016)
Background The aim of the study is to report on a new technique for applying the eSVS Mesh (Kips Bay Medical, Minneapolis, Minnesota, United States), an external saphenous vein support system, without the use of fibrin sealant.Methods The mesh covers the entire body of the graft with the exception of both anastomoses. Fibrin sealant was not used to fix the mesh. Two patients underwent surgery using this preparation.Evaluation At 4 weeks, computed tomographic angiography revealed no signs of mesh compression at either anastomotic area. The proximal anastomosis inflow diameter was greater than the diameter of the mesh-supported body of the graft.Conclusion This technique successfully eliminates the need for the use of sealant and supports favorable anastomotic geometry.
Keywords: eSVS mesh; vein graft patency; operative technique